Star attractions : twentieth-century movie magazines and global fandom - McDonald, Tamar Jeffers; Lanckman, Lies, 1988- (Fandom & culture., 2019)
"This first of its kind examination turns the spotlight on the fan magazines of the "classic Hollywood" era, which famously fed obsessions with celebrities such as Mae West and Elvis Presley. In their heyday, from the 1920s to the 1950s, about twenty major fan magazines were on offer every month at American newsstands, with even more offered in other countries. However, film studies scholars often still regard these publications with suspicion, perhaps due to the magazines' reputation for purveying scandal and gossip, and their frequent mingling of gushing tone and blatant falsehood. However, by treating these movie magazines as primary sources, the contributors are able to gain unique insights into contemporary assumptions about the relationship between fan and star, performer and viewer. As a result, they find these fan magazines to be a huge and hitherto largely untapped resource on a wealth of subjects, including appropriate gender roles, appearance and behavior, and national identity. Essayists address three key areas: the variety of periodicals published under the movie or fan magazine rubric; the magazines' widespread emphasis on stars, fans, and the interaction of the two; and international variations on the original American model. Combining innovative scholarship with an entertaining subject matter, this collection on an understudied yet powerful cultural medium is sure to appeal to film, media, fan, and popular culture studies scholars alike, not to mention film buffs of Hollywood's "golden era.""--